Smart city as a social transition towards inclusive development through technology: a tale of four smart cities. (1st January 2023) - Lee, Juhyun; Babcock, Julia; Pham, Thai Son; Bui, Thu Hien; Kang, Myounggu
ABSTRACT: Smart city initiatives have the potential to address many contemporary urban challenges, utilizing information and technology. Increasingly, smart cities are considered as social innovation processes to achieve sustainable and inclusive urban development, being influenced by broader socio-economic and institutional contexts of cities. This paper explores 'smart city transitions' across varied urban contexts, in particular, how smart city transitions are enacted and how they contribute to inclusive urban transformation and public value. Using a multiple case studies approach, the research investigated infrastructure planning practices in Amsterdam in the Netherlands, Seoul in Korea, Portland in the U.S. and Ho Chi Minh City (HCMC) in Vietnam, cities that were known for strong efforts to establish integrated platforms to enhance societal benefits. Our analysis showed that each city has addressed its goals around sustainability, equity and affordability by reinforcing the engagement of multiple actors with the support of integrated platforms that facilitate open and multi-directional information flow in a transparent manner. In Amsterdam, innovative solutions for sustainable use of resources have been invented and distributed through multi-level social networks, contributing to the transformation into a circular economy. In Seoul and HCMC, the city's persistent efforts to utilize an open and integrated platform resulted in proactive engagement and collaboration of public and private actors in improving quality, equity and efficiency of transit services. Portland has tackled inequitable access and mistrust issues by setting principles for data governance and facilitating equity in the adoption of innovative technologies. Our research revealed that four cities established different forms of integrated platforms such as a centrally-controlled platform and a community-centred platform in order to address specific socio-economic issues within an institutional setting of each city. We concluded that building an integrated platform is not easy, but it is a critical prerequisite for the process of sustainable transformation to truly achieve smart cities across the globe.